Competitiveness of human and business in terms of stock market analysis - Ihor Hurnyak; Pedro Pardal; Veronika Machová; Jakub Horák (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
The competitiveness of modern human and business are inextricably linked with the work of the stock market. In some cases, easily could be detected a correlation between trends or tendencies of the stock market and the directions of transformation of human behavior. What should people and businesses be like to maintain this competitiveness at the proper level? According to the authors, it is the developed stock market as instrument of modern society that provides the answer to this question. Through the analysis of stock markets tendencies, this research aims to find evidence that confirm the new characteristics of human life in the fields of education, healthcare, communication, commerce, and interaction with virtuality. Most researchers focus separately on the study of human behavior and the functioning of the stock market. We analyze the relation between both dimensions, assuming that the stock market can be considered, for developed countries, through the small investors voting as public preferences and goals reflection. Evidence from statistical analysis of the stock market confirmed the following characteristics of modern human: faster dissemination of knowledge, e-commerce acceleration, influencing interpenetration of the Internet communications, in depth virtualization, and accelerated circulation of information flows. Operating within such flows of change allows people and businesses to remain competitive at the appropriate level.
Keywords: D02; D91; I112; I21; M21; 330; New Human; Pandemic Influence; Virtualization; Remote Education; Stock Market; Competitiveness